How do parents approach nighttime infant care? A grounded theory - Dooner, Caryn; Ou, Christine; Kim, Hana; Marcellus, Lenora; Henry-Dansereau, Michaela; Sidhu, Jessy (Frontiers in Sleep, 2026)
IntroductionHow parent dyads organize and share nighttime caregiving, particularly in the context of gender-roles and diverse family structures, has been given little attention. The aim of this study was to develop a grounded theory explaining how parent dyads manage nighttime infant care, focusing on caregiving practices, decision-making, and their effects on parental roles and well-being.MethodsParent dyads with children under 2 years of age who completed an online questionnaire were invited to participate in virtual semi-structured interviews about their nighttime caregiving approaches. Interview transcripts were analyzed using constructive grounded theory methods.ResultsTwenty cisgender heterosexual and 10 2SLGBTQ+ dyads were interviewed. The core category navigating priorities was identified, which highlighted the tension created by competing demands and priorities. Parents responded by either staying the course—maintaining their current approach—or changing lanes—adopting a new strategy—within their unique dyadic context. This context encompassed the characteristics and evolving experiences each person brought to their family. This iterative process was triggered whenever tension arose from competing values or priorities.DiscussionDyadic context shapes how couples navigate nighttime care priorities. Flexibility in decision-making and active engagement from both partners in adapting to evolving needs promoted mutually supportive nighttime caregiving for families. These findings enhance understanding of shared parenting dynamics in diverse family structures, informing strategies to support parental and infant sleep and well-being.